Из истории русского старожильческого населения Литвы - Сивицкене, Мария (Kalbotyra, 1997)
The author studies the time period and reasons for the appearance of the Russian population in Lithuania. The analysis is based on historical facts and late statistics. The article especially treats the localization of the Russian old believers in Lithuania and neighbouring territories and gives statistics concerning the Russian population in Lithuania.